De Salem a Eastwick: a figura da bruxa na representação da presença feminina - Oliveira, Amanda Laís Jacobsen de (2021)
This research has grown out of some anguishes. Far from solving them, this work maybe add some others. However, at least now I can trace and outline their path. There is a saying that tells us that ignorance is a blessing. From my research, I consistently state to disagree with this assertion. The one who does not know also suffers, only he/she does not know the reasons of his/her afflictions. I chose to know it in order to try to uncover and unmake its plot, thinking of weaving new ones. Weaving, because it is the way it is done in the text, in narrative. For centuries, the culture has constituted and perpetuated a stereotyped image of women. This image puts woman in a place assigned to her by the patriarchal world. Representation not only represents the existent in the referent world, it also creates this world. We identify and understand ourselves and the society in which we are integrated based on representations. Therefore, this work studies the relations among witches characters’ representations in two narratives, with our comprehensions of women through history and, mainly, in contemporaneity. It is a literary research analyzing John Updike’s novel, The Witches of Eastwick (1984), and Arthur Miller’s dramatic text, The Crucible (1953). Both narratives are here taken as cultural artefacts or narrative artefacts, having as basis narratology’s fundaments as expressed by Mieke Bal. It as an interdisciplinary analysis, coordinating history, literary criticism, narratology and philosophy readings. This work’s fundamental essence, or its Mother structure, is the feminist reading in front of narratives written by men authors. I have pointed out the ways in which these perpetuated and reproduced narratives bring a woman that is object, with no place to be subject of her own history. When she does it, she is judged in a way it makes impossible to readers to identify with her. To think of a feminist reading, considerations of Joan Scott, Judith Butler, Donna Haraway, Luce Irigaray, Thomas Laqueur, Teresa de Lauretis, Shulamith Firestone, Mary Daly, Jonathan Culler and Antoine Compagnon were essential. Furthermore, in order to comment on the witch’s figure through history Silvia Federici’s text became a direction to the structure of the text. With it are Nubia Hanciau and Carlo Ginzburg’s texts, as well as the Malleus Maleficarum. The first part of the thesis is the reading and connection of feminist theories and criticism that have oriented my research all the way; the compendium of critical readings of both narratives; and considerations about narratology that have helped while looking at the narrative elements to the study (character, narrator, focalizer). The second and last part (bigger in its extension) has three chapters of analysis that display the phallocentric construction of the witch and of woman in this world made by and to white men. In these chapters the focus is the witch’s figure, expressing the impossibility in setting apart the comprehension of the woman in our social, historical and cultural context, from this so instigating supernatural figure.